Analisa Perbandingan Keefektipan Waktu Proses Perhitungan Metode SAW dan WP Dalam Menentukan Siswa Berprestasi - Wulan, Nur; Dafitri, Haida; Sihombing, Ermayani (Universitas Islam Negeri Sumatera Utara, 2022)
Achievement students are the achievements of every student in school, stand out among other students and sent to take part in the competitions with the name of the school becoming a student pride. The process of achieving achievements that still uses a manual system that actually less effective in student achievement. Therefore, the author designed decision support system comparative analysis between the two methods Simple Additive Weighting (SAW) and Weight Product (WP) with criteria that have been determined criteria. These two methods are compared to find out which method is more effective in the calculation process which is expected to help in determining students achievers.Keywords: SPK; SAW; WP; Achievement; School